SAMPLING AND REPRESENTATIVENESS IN CORPUS CONSTRUCTION - Turg’unova Marjona, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Abstract: The creation of linguistic corpora is a vital aspect of linguistic research, allowing scholars to analyze language use in various contexts. This article explores the principles of sampling and representativeness in corpus construction, highlighting their significance in ensuring that linguistic data accurately reflects real-world language use. Through examining different sampling methods and their implications for representativeness, this paper aims to provide a clear understanding of how these factors impact linguistic analysis and findings.